Topological insights from state manipulation in a classical elastic system - Kazi T. Mahmood; M. Arif Hasan (AIP Advances)
The exploration of the Berry phase in classical mechanics has opened new frontiers in understanding the dynamics of physical systems, analogous to quantum mechanics. Here, we show controlled accumulation of the Berry phase in a two-level elastic bit, which is a classical counterpart to qubits, achieved by manipulating coupled granules with external drivers. Employing the Bloch sphere representation, the paper demonstrates the manipulation of elastic bit states and the realization of quantum-analog logic gates. A key achievement is the calculation of the Berry phase for various system states, revealing insights into the system’s topological nature. Unique to this study is the use of external parameters to explore topological transitions, contrasting with traditional approaches focusing on internal system modifications. By linking the classical and quantum worlds through the Berry phase of an elastic bit, this work extends the potential applications of topological concepts in designing new materials and computational models.